The main role of marketing in tourism industry (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Marketing toward tourists is about showing them how they can temporarily escape their normal, hectic lives for a change of venue and entertainment. The purpose behind tourism marketing is to promote the business, make it stand out from rivals, attract customers, and generate brand awareness.